Canopy cover, biomass production and nutrient accumulation by coper crops (Revista de Ciências Agroveterinárias, 2016)
The use of cover crops is an important strategy for maintaining the productive capacity of agricultural land. This research aimed to determine the soil coverage, biomass production and accumulation of N, P, K, Ca and Mg in plant tissue of different species of cover crops on the southern plateau of Santa Catarina, Brazil. The experiment was conducted in a Humic Cambisol (Inceptisol) with the following treatments: i) BO - black oat (Avena strigosa); ii) WR - wild radish (Raphanus sativus L.); iii) CV - common vetch (Vicia sativa); iv) IS - intercropping of the three species; and v) WF - winter fallow with spontaneous vegetation. The use of cover crops has potential for high biomass production, canopy cover and nutrient accumulation by plant tissue, higher than winter fallow. In the early stage of plant development the highest growth rates and soil coverage occur in WR and IS, while at the end are higher in CV and IS. The crops of BO, CV and IS produce large amounts of dry shoot mass and BO produces greater dry root mass. In general, the CV and IS treatments and the shoot accumulate greater amounts of nutrients in plant tissue as compared to other treatments and the roots, respectively.
Keywords: Soil conservation; intercropping cover crops; green manure; nutrient cycling.